Bridging the Gap Between Nutritional Knowledge and Iron Intake Adequacy in Medical Students - Amalia, Azka; Hartoyo, Arya Pradipa Airlangga; Cholidah, Rifana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Iron deficiency anemia remains a significant global health issue, particularly among young adults. Medical students are theoretically expected to possess superior nutritional literacy compared to the general population due to their academic exposure to metabolism and digestive systems. However, a gap often exists between theoretical knowledge and daily dietary practices. This article reviews the literature regarding the relationship between nutritional knowledge levels and iron intake adequacy. The review highlights that nutritional knowledge involves cognitive levels ranging from recalling information to evaluation. Iron metabolism is complex, involving heme and non-heme iron absorption, which is significantly influenced by enhancers and inhibitors. Despite having high nutritional knowledge, medical students' eating behaviors are increasingly determined by modern lifestyle factors, including social media trends and fast-food consumption, which may compromise iron intake. Conclusively, bridging the gap between knowledge and practice requires not just memorization but the application of balanced nutrition principles (Tumpeng Gizi Seimbang) to ensure optimal iron bioavailability.